2014
DOI: 10.1111/jvh.12282
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A virus in the Middle East and North Africa region: a new challenge

Abstract: During the past three decades, a gradual shift in the age of infection with hepatitis A virus (HAV) from early childhood to adulthood has been observed. There is a general lack of updated data on HAV burden of disease, incidence and age-specific seroprevalence in countries of the Middle East and North Africa (MENA) region. The aim of this article is to review the published data on anti-HAV seroprevalence, an important tool to monitor infections rates, in countries of the MENA region and associated risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 54 publications
4
41
1
Order By: Relevance
“…HAV is still endemic in Tunisia, with a high/intermediate ranking (4,12,31,36,37), and in the Mediterranean region (8,38,39). Despite the potential public health hazard linked to the use of contaminated treated sewage, few studies have been carried out on the prevalence of HAV in wastewater and its seasonal and geographical distribution in Tunisia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HAV is still endemic in Tunisia, with a high/intermediate ranking (4,12,31,36,37), and in the Mediterranean region (8,38,39). Despite the potential public health hazard linked to the use of contaminated treated sewage, few studies have been carried out on the prevalence of HAV in wastewater and its seasonal and geographical distribution in Tunisia.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its nonenveloped nature, HAV is very stable in the environment for long periods and is particularly resistant to the current wastewater treatment processes (10,11). Even though Tunisia has developed its secondary sewage treatment plants (12), the quality of treated wastewater is still poor (13). Unfortunately, Tunisia, among other Mediterranean countries with high endemicity of HAV infections, is using contaminated treated wastewater for irrigation and to refill aquifers to palliate the lack of water resources (14), which may pose a real threat for public health.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite its prevalence across the world, updated data about HAV infections in the ME, including their burdens and seroprevalence, are limited. It has been reported that a slow shift in the age of infected subjects from childhood to adulthood has been observed (14). The hepatitis D virus (HDV) appears to be endemic in the ME region (15), and the hepatitis E virus is reported to have a prevalence ranging from 2.0% to 37.5% in countries of the ME and North Africa (16).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 32% of hemodialysis patients in countries within the purview of the Eastern Mediterranean Regional Office of the World Health Organization (WHO) have acquired HCV infections (13). Furthermore, other countries neighboring the ME such as Pakistan and Azerbaijan have a considerable rate of HCV infections (11,14), and these rates can directly influence those within the ME region.…”
Section: Introductionmentioning
confidence: 99%